The complement cascade in lung injury and disease - M. G. Detsika; K. Palamaris; I. Dimopoulou; A. Kotanidou; S. E. Orfanos (Respiratory Research, 2024)
Abstract Background The complement system is an important arm of immune defense bringing innate and adaptive immunity. Although originally regarded as a major complementary defense mechanism against pathogens, continuously emerging evidence has uncovered a central role of this complex system in several diseases including lung pathologies. Main body Complement factors such as anaphylatoxins C3a and C5a, their receptors C3aR, C5aR and C5aR2 as well as complement inhibitory proteins CD55, CD46 and CD59 have been implicated in pathologies such as the acute respiratory distress syndrome, pneumonia, chronic obstructive pulmonary disease, asthma, interstitial lung diseases, and lung cancer. However, the exact mechanisms by which complement factors induce these diseases remain unclear. Several complement-targeting monoclonal antibodies are reported to treat lung diseases. Conclusions The complement system contributes to the progression of the acute and chronic lung diseases. Better understanding of the underlying mechanisms will provide groundwork to develop new strategy to target complement factors for treatment of lung diseases.